ANALISIS KEMAMPUAN MAKEUP ARTIST MENGIDENTIFIKASI KONDISI KULIT KLIEN DITINJAU DARI LATAR BELAKANG PENDIDIKANNYA - Sevia, Shafa Adrine; Ihsani, Ade Novi Nurul (Universitas Negeri Surabaya, 2022)
Makeup Artist is a profession that requires skill. The ability to apply makeup can be obtained through formal, non-formal, or informal education. A Makeup Artist must not only have the ability to apply makeup to clients but also to identify their skin conditions, which will affect the treatment that should be applied to each different skin condition. The purpose of this research is to determine the ability of Makeup Artists with formal (university), non-formal, and informal education backgrounds to identify skin types. The research subjects were people who worked as Makeup Artists in Semarang with a minimum of 1 year of experience. Data collection techniques used in this research were interviews and questionnaires. Data analysis was performed using descriptive statistics. The results showed that in formal, non-formal, and informal education, the dominant category level was moderate, with an average percentage above 60%, indicating that the Makeup Artists' ability to identify clients' skin conditions was good. However, upon closer examination, there were slight imbalances in the low and high levels. It was found that Makeup Artists with formal and non-formal education were more superior in terms of theory, attitude, and practical skills in applying makeup to clients with different skin conditions.Keywords: MakeUp Artist, Education, Competence Indicator